Sharia Business Ethics Fight for a More Sustainable Post-Pandemic Recovery - Muhamad Rahman Bayumi; M. Junestrada Diem; Rizal Alfit Jaya (Yayasan Riset dan Pengembangan Intelektual, 2023)
Sharia business ethics is a set of normative moral principles originating from Islamic law to regulate what should be done and what should not be done. The authenticity of the Islamic teaching system is often misunderstood, misinterpreted, and even facilitated when faced with various business problems that make these activities far from achieving maqashid sharia. The rise of crime during the pandemic disrupted the stability of life. As a country with the largest Muslim population, Indonesia should be the safest country in the world because of the perfection of its religious teachings, which regulate ways of life, socializing, the economy, politics, and all the details of life. This study provides a conceptual description of the re-contextualization of sharia business ethics to achieve more sustainable goals. The question in this research is how to re-contextualize Islamic business ethics in the success of economic activities to improve the order of life starting from the grassroots level to the top level. The findings in this study describe the concept of Islamic business ethics that is applicable, integrative, and interconnected. This research is expected to offer a description, design, policy, and sustainable contract model for policymakers to accelerate and improve life after the pandemic.